2018
DOI: 10.3390/ijerph15010086
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Location–Routing Problem for Cold Chain Logistics Considering Carbon Footprint

Abstract: In order to solve the optimization problem of logistics distribution system for fresh food, this paper provides a low-carbon and environmental protection point of view, based on the characteristics of perishable products, and combines with the overall optimization idea of cold chain logistics distribution network, where the green and low-carbon location–routing problem (LRP) model in cold chain logistics is developed with the minimum total costs as the objective function, which includes carbon emission costs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 29 publications
(32 reference statements)
0
119
0
Order By: Relevance
“…Parasuraman et al [38] constructed a distribution route optimization model with the lowest carbon emissions as the objective and based on the necessity of energy saving in cold chain logistics vehicle distribution. Wang et al [39] considered the differences in energy consumption between the transportation and unloading processes caused by the opening of the refrigerated door, and established the optimal distribution route model of fresh agricultural products in terms of carbon emissions and with the objective of generating the lowest cost.…”
Section: Research Considering Carbon Emissionsmentioning
confidence: 99%
“…Parasuraman et al [38] constructed a distribution route optimization model with the lowest carbon emissions as the objective and based on the necessity of energy saving in cold chain logistics vehicle distribution. Wang et al [39] considered the differences in energy consumption between the transportation and unloading processes caused by the opening of the refrigerated door, and established the optimal distribution route model of fresh agricultural products in terms of carbon emissions and with the objective of generating the lowest cost.…”
Section: Research Considering Carbon Emissionsmentioning
confidence: 99%
“…Finally, they conducted a case study to demonstrate the applicability of the model. Wang et al studied the LRP for cold perishable products considering GHG emissions. They implemented a hybrid genetic algorithm to solve a practical numerical example to validate their proposed methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al [22] took the consumption rate of vehicle fuel as the breakthrough point, and found the model considering the fuel consumption rate was significantly lower than the traditional VRP model in terms of fuel consumption. Wang et al [23] proved that carbon tax policy can effectively reduce carbon dioxide emissions in cold chain logistics network through numerical examples. Ericsson et al [24] quantified the carbon emissions by driving distance, and constructed a model aiming at minimizing carbon emissions.…”
Section: Introductionmentioning
confidence: 99%